Oh, wait, O8 de Sitter may be unstable! - Iosif Bena; G. Bruno De Luca; Mariana Graña; Gabriele Lo Monaco (Journal of High Energy Physics, 2021)
Abstract We analyze the stability of four-dimensional de Sitter vacua constructed by compactifying massive Type IIA supergravity in the presence of two O8 sources [1]. When embedded in String Theory the first source has a clear interpretation as an O8− plane, but the second one could correspond to either an O8+ plane or to an O8− plane with 16 D8-branes on top. We find that this latter solution has a tachyonic instability, corresponding to the D8 branes moving away from the O8 − plane. We comment on the possible ways of distinguishing between these sources.